Evaluation of the Effect of Different Glazing Brands on Surface Roughness of Monolithic Zirconia - Riyam Imad Fouad; Lateef Essa Alwan Al Jorani; Abdel Kareem Jasim Khadim Al-Azzawi (Journal of Techniques)
The effect of glazing on the mechanical properties of monolithic high translucent zirconia is widely used to fabricate highly aesthetic and strong dental restorations using CAD-CAM technology. The purpose of this study was to evaluate the surface roughness of different glazing brands' materials on monolithic Zirconia. 40 specimens from Zirconia block (VITA YZ®XT Color, Diameter 98.4x14mm height) were prepared by computer-aided design/computer-aided manufacturing machined (Imes-Icore, 5 axis, COR TEC 250i dry, Germany). The samples dimension for the surface roughness test (diameter 10 mm and thickness 2 mm) by using a surface roughness testing machine profilometer (TR200, Germany), divided into 3 groups depending on types of glazing brands materials (VITA, VITA AKZENT® Plus, glaze LT, Germany), the second group with (Ivoclar Vivadent, IPS e.max Ceram glaze and stain liquid, Liechtenstein), and the third group with (GC Initial spectrum glaze liquid, Austria). The data were analyzed statistically using the package for social science, (ANOVA) test with the Bonferroni test to accept or reject the statistical hypothesis. For the roughness readings, the GC group had the greatest mean value of surface roughness in zirconia (0.721±0.014), followed Ivoclar group (0.663 ± 0.030), and then the VITA group (0.641±0.021). There was a statistically significant difference between (VITA&GC) and (Ivoclar & GC) with a p-value < 0.05, except between VITA with Ivoclar, there was no statistically significant association with a p-value > 0.05 for both. Zirconia glazed with GC paste (powder, fluid) has higher surface roughness than samples glazed with Ivoclar paste (powder, fluid) followed by the VITA group which has lower surface roughness. The results concluded that the monolithic zirconia glazed with GC glaze material displays a higher surface roughness than Ivoclar and VITA glaze.